(untitled) (Journal of actual problems of jurisprudence, 2018)
The scientific article is devoted to the study of some of the issues of intellectual property in commercial activities. The author analyzed the state of regulatory support use of intellectual property, identified problems in this sphere and the main directions of research. Key words: intellectual property, intellectual property law, intellectual property objects, commercial use.